Constitutionality of Presidential Threshold Application in Indonesia's Presidential Election System: Analysis of Constitutional Court Decision Number 90/PUU-XXI/2023 - Bram B Baan (Research Horizon, 2025)
This study examines the constitutionality of presidential threshold implementation in Indonesia's presidential election system through a comprehensive analysis of Constitutional Court Decision Number 90/PUU-XXI/2023. The presidential threshold, regulated in Article 222 of Law Number 7 of 2017 concerning General Elections, requires political parties to obtain a minimum of 20% of seats in the House of Representatives or 25% of valid national votes to nominate presidential and vice-presidential candidates. Employing qualitative legal research methods, this study analyzes the legal considerations, constitutional implications, and democratic principles underlying the Court's decision. The research reveals that while Decision 90/PUU-XXI/2023 addressed age requirements for presidential candidates, it reflects the Court's evolving jurisprudence on electoral justice and constitutional rights. The findings demonstrate that presidential threshold provisions have been repeatedly challenged before the Constitutional Court, with petitioners arguing violations of morality, rationality, and intolerable injustice. The Court's inconsistent positions across multiple decisions highlight tensions between open legal policy doctrine and constitutional guarantees of political rights and popular sovereignty. This research contributes to understanding constitutional interpretation dynamics in Indonesia's democratic electoral system and provides insights into the balance between political stability objectives and inclusive democratic participation.